High-quality genomic DNA extraction methods of Yellow Spathoglottis Blume complex for next-generation sequencing (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Jasim JHM, Othman AS, Nordin FA, Talkah NSM. 2024. High-quality genomic DNA extraction methods of Yellow Spathoglottis Blume complex for next-generation sequencing. Biodiversitas 25: 654-663. Advancements in genomic research have spurred a growing interest in extracting high-quality genomic DNA, particularly from intricate plant species like the Yellow Spathoglottis Blume Complex. The preparation of genomic DNA high-quality from a plant sample is a crucial step for genomic and genetic analysis studies. A variety of genomic DNA extraction methods such as the traditional Hexadecyltrimethylammonium Bromide (CTAB) method and commercially available kits have been reported. Even so, they are either low purity and yield or costly. We develop a good-quality genomic DNA extraction method from fresh and dried leaves of the Yellow Spathoglottis Blume complex in Peninsular Malaysia, specifically tailored for Next-Generation Sequencing (NGS) applications. Three DNA extraction methods were compared traditional CTAB, modified CTAB, and the DNeasy Qiagen plant mini kit methods. The yield and quality of extracted DNA were assessed by PCR amplification using nuclear ETS and ITS genes performed to evaluate the success of DNA extraction. Additionally, the suitability of the modified CTAB method for NGS library preparation and sequencing was tested. It demonstrated better PCR amplification results, yielding high-concentration bands for both ETS and ITS primers. Furthermore, the modified CTAB method proved suitable for high molecular weight DNA extraction, without contamination. The extracted DNA from Spathoglottis aurea exhibited high molecular weight and passed the quality control assessment for NGS library preparation. Sequencing results demonstrated an average quality score of 36.0, with an accurate base call rate of approximately 99.9%. The developed method enables reliable genomic analysis and sequencing of the Yellow Spathoglottis Blume complex, contributing to further research and understanding of this species group.